A different perspective, a different way of sharing knowledge in the math classroom (2020)
This article seeks to encourage math teachers to reflect on the social, political and cultural role of everyday activities in the classroom. To this end, the political connotation of the teaching of mathematics and the socio-political perspective, as another way of guiding and sharing knowledge, are highlighted. The discussion on the political connotation of the area of mathematics provides an overview of the monoculture of knowledge that permeates teaching in regular schools and turns the school scenario into a replicator of the hegemonic culture, which determines what knowledge to teach and what not to teach. Then, theimportance of teaching mathematics from critical pedagogy is analyzed, since every action in the classroom is political and has social impact. Finally, pedagogical strategies are explored to bring students and educators closer to mathematical knowledge from a reflective andcontextual practice, as a strategy to achieve cultural mathematics.